An Interpretation of Biological Development - Coutts, Jason (My University, 2020)
The research programs and practices used to address biological problems are often grounded in the way one interprets biological organisms. There is a practical motive to explain organismic development in terms of genes and the environments in which genes are expressed. This interpretation presupposes that organisms are simply gene environments. In this way, genes either control the outcome of development or contain information that specifies particular outcomes. In either case, development is basically a problem to be resolved through an increased understanding of genes and the ways genes are expressed. This interpretation fails to adequately explain the process by which complex form is generated. Therefore, there are grounds for rejecting it. An approach centred around the whole organism directs attention towards its many constituents and requires that one take seriously the role of multiple organismic elements in order to adequately explain development.